Japanese Parents’ Explanations of Disabilities to Siblings of Children with Intellectual and Developmental Disabilities - Hiroki Yoneda; Kana Miura (Journal of ICSAR, 2021)
One form of support that has been demonstrated to reduce psychological burden in siblings of children with intellectual and developmental disabilities is an explanation of the disability. By clarifying the actual conditions in which parents explain their child’s disability to siblings, the goal of this study is to support parents in promoting open communication in the family environment. A semi-structured interview was conducted with five parents of children with disabilities aged 2–6 years who were attending daycare or preschool at private educational institutions. Interviews were analyzed using a grounded theory approach. A primary reason for parents explaining their child’s disability to siblings was their belief that siblings may already have known about the disability, and they wanted to answer any questions that may have arisen. After parents explained the disability, some mothers noticed no changes in the siblings, but others reported that siblings asked more questions about the child with disabilities and expressed a desire to help support them. It is recommended that Japanese parents of children with disabilities receive information on available support systems provided by educational institutions and government/administrative agencies.